ANALISIS MATERI AJAR DARI LAMAN WEB WWW.SCHUBERT-VERLAG.DE UNTUK PEMBELAJARAN MENYIMAK BAHASA JERMAN SISWA SMA - Bella Fitriasari, Ghista (LATERNE, 2017)
Listening comprehension is a skill that must be mastered because it will be a means in the communication process to get oral information. When listening to German at school, listening comprehension has some obstacles. These include the selection of the appropriate teaching materials to help the pupils to reach the competence and determine the problem with the source of teaching material. But together with the development of information and communication technology the Internet will be the source of the teaching material that can be applied. Some German websites appear. And they offer teaching materials that can help the pupils learn German. Of many types of websites www.schubert-verlag.de is a website which will be a source to get the teaching materials. This website provides free teaching materials and exercises. The teaching materials and exercises are published from the books of Schubert Verlag. The problem with this study is